Antibacterial finishing on cotton 100% and CVC fabrics with tannin from Piper betle extract - Huong, Bui Mai; Hue, Trinh Thi Kim (Vietnam Journal of Science and Technology, 2019)
Following the recent trend of using natural ingredients from bio-macromolecules, biomaterials, plant extract in textile chain, this research aims to develop an antibacterial textiles finishing with Tannin extracted from piper betle plant. The extracting processes were carried out with different solvent: distilled water, Ethanol 30%, Ethanol 50%, Ethanol 70% in 60 minutes. Two important types of fabric, including Cotton and CVC (Cotton/Polyester) were padded with piper betle extracts, then dried at 60oC in 5 minutes. The presence of tannin on fabric after treatment was determined by FeCl3 test and FT-IR spectrum. The antibacterial effect of finished fabrics was proved according to ASTM 2149-01 standard. The test was performed with Escherichia Coli ATCC 25922 and Staphylococus aureus AATCC 6538. The final results exhibited good antibacterial activity of 83.02%, 65,33% against the bacteria Ecoli and 93.88 %, 85.14% against the bacteria S.Aureus on cotton and then CVC fabrics.